The past, present and future of Pite Saami: sociological factors and revitalization efforts - Valijarvi, R-L; Wilbur, J (2011)
Our paper is a report on the past, current and future state of the endangered Pite Saami language (aka: Arjeplog Saami) spoken in Swedish Lapland. Our primary data come from interviews with Pite Saami individuals and our field observations. We estimate the vitality of Pite Saami based on the UNESCO Language Vitality Scale, taking into consideration factors such as the number of speakers, language attitudes and the quality of documentation. We also discuss the possible reasons for the decline of Pite Saami, report on the speakers’ views of other Saami languages and Swedish, consider whether there is a specific Pite Saami identity, describe revitalization efforts already taking place, and discuss the future prospects of the language.